CITIZENSHIP PRACTICE AND INTERPERSONAL RELATIONS IN THE CONTEXT OF PHILOSOPHICAL AND ORGANIZATIONAL: A STUDY OF CASE IN UESPI- CAMPUS TORQUATO NETO (Fiep Bulletin - online, 2011)
This article aims to address the citizenship and interpersonal relationships in the philosophical context and organization.It is necessary to highlight the philosophy of the organization as a set of principles and policies forces and attitudes that help communicate the goals, plans and funcionários.A rules for citizenship is conceived as a strategy in order to build a better society. In this context the interpersonal relationships aim to bring the employee satisfaction and pleasure in the organizational field, with an appreciation and recognition for performance. Thus it is essential to professional ethics within the organization regarding the behavior and performance of employees at work.Were realized bibliographical researchs in books and field researchs with 30 employees of UESPI-Campus Torquato Neto,in the first semester of 2010
Keywords: Organization; Citizenship; Interpersonal relationships